2012
DOI: 10.1200/jco.2012.43.2278
|View full text |Cite
|
Sign up to set email alerts
|

Risks of Less Common Cancers in Proven Mutation Carriers With Lynch Syndrome

Abstract: A B S T R A C T PurposePatients with Lynch syndrome are at high risk for colon and endometrial cancer, but also at an elevated risk for other less common cancers. The purpose of this retrospective cohort study was to provide risk estimates for these less common cancers in proven carriers of pathogenic mutations in the mismatch repair (MMR) genes MLH1, MSH2, and MSH6. Patients and MethodsData were pooled from the German and Dutch national Lynch syndrome registries. Seven different cancer types were analyzed: st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
208
0
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(238 citation statements)
references
References 29 publications
17
208
0
13
Order By: Relevance
“…The cumulative risk at age 70 was 9.1% (95% CI: 4.4-13.8). 8 The two patients who provided prostate tumor tissue for testing had mixed results, with the prostate tumor from patient 4 (deletion of exons 1-6 in MSH2) exhibiting both loss of protein expression and MSI, whereas the prostate tumor from patient 6 (deletion of exon 8 in MSH2) had intact protein expression and microsatellite stability. We conclude that although impaired MMR function may contribute to prostate cancer development in some cases, it is unlikely to do so in all cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cumulative risk at age 70 was 9.1% (95% CI: 4.4-13.8). 8 The two patients who provided prostate tumor tissue for testing had mixed results, with the prostate tumor from patient 4 (deletion of exons 1-6 in MSH2) exhibiting both loss of protein expression and MSI, whereas the prostate tumor from patient 6 (deletion of exon 8 in MSH2) had intact protein expression and microsatellite stability. We conclude that although impaired MMR function may contribute to prostate cancer development in some cases, it is unlikely to do so in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…4 Prostate and breast cancer are currently not considered part of the LS tumor spectrum. Some studies have revealed an increased incidence of prostate cancer, especially in patients carrying an MSH2 mutation, [5][6][7][8] whereas others have not shown an increased incidence. 2,9,10 Two studies have shown a lack of MMR protein expression in prostate cancer tumors in patients with LS.…”
Section: Introductionmentioning
confidence: 99%
“…The syndrome is characterized by inheritance of a germline mutation in genes of the DNA mismatch repair system, namely, MLH1, PMS2, MSH2, or MSH6, which are mutated in differing frequencies (26)(27)(28). Patients with Lynch syndrome-associated ovarian cancer have a mean age at presentation of 48 years (compared with a median age of ~68 years in those without Lynch syndrome), with approximately 50% of patients having stage I cancer.…”
Section: [H2] Risk Factorsmentioning
confidence: 99%
“…23 Individuals with Lynch syndrome also are predisposed to other cancers, such as urothelial cancers, small bowel cancer in men, and breast cancer in women. 24 For individuals identified as HNPCC mutation carriers, annual/biennial colorectal screening with colonoscopy is recommended from age 20 years, and yearly gynecologic examination with transvaginal ultrasound is recommended for women starting at age 30 years. 25 If they have an adenomatous polyposis coli (APC) gene mutation, then individuals with FAP have a nearly 100% risk of colon cancer.…”
Section: Introductionmentioning
confidence: 99%